Literatura, ideologia e política: uma proposta de abordagem psicossocial sobre a literatura de Jorge Luis Borges durante o primeiro governo de Juan Domingo Perón (1946-1955) - Mello, Felipe Carvalho Correa de (2010)
The presente research has as primay objective an interpretation about the literature of Jorge Luis Borges grounded in a teorical and metododological aproach concerned to Social Psychology. In this way, we propose the use of the concept of ideology developed by J. B Thomposn, and the concepts of literary field by Bourdieu and discursive poliphony by Mikhail Bakhtin. We propose an analisys and an interpretation of the Borges literature that iluminates its political dimension and not only aesthetic. We propose to describe the production, circulation and reception of his literature along the peronistas years (1946-1955), and in wich ways the literature had articuleted with the conflicts between the peronista State and the argentinian literary field during this years